The semiology and classification of myoclonias. - Almeida, R (1995)
Myoclonus can present itself in various distinct clinical contexts. The authors review the possible different types of myoclonus, as a single manifestation or included in a syndrome, based on a semiological and aetiological classification. Special emphasis is given to the group of progressive myoclonus epilepsies.